Penggunaan Media Ceker pada Operasi Bilangan Bulat untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas IVB SDN 31 Tampan Kodya Pekanbaru (Jurnal Pilar Sains, 2005)
This research starting from experience that a lot of constraint of Mathematics study at Elementary School(SD) in this case about readiness of bouncing teacher. Do not ready to bounce the teacher in submittinginteger items, Namely (1) Difficulty explain the items of like operation (-4)-(-6), (2) Difficulty give theanswer realistic go together the integer operation, (3) Do not know the media of what applicable to explainthe integer operation. Refering to that main problem studied in this research is “Whether/What use ofmedia ceker at integer operation can improve the result learn the mathematics of student of alas of IVBSDN 031 Tampan Of Kodya Pekanbaru?” Subjek Research is student of alas IVB SDN 031 Tampan ofKodya Pekanbaru. Research executed by kolaboratif to student (final duty) and class teacher.Researchsdata collected is form of quqntitqtive data namely test the (block evaluation, and tes final subject study)and also data qualitative in the form of perception to activity of student and teacher. Data analyzeddescriptive by criteria is complete result of learning and description of frequency of activity of student andteacher. From analized can concluded that “using of media ceker at integer operation can improve theresult learn the mathematics of student of class IVB SDN 031 Tampan of Kodya Pekanbaru. Execution ofUse of Media Ceker in class designed in study peripheral and analyze result of perception showed thatexecuted as according to study planning.